2003
DOI: 10.2741/1041
|View full text |Cite
|
Sign up to set email alerts
|

Activity rhythms and orientation in sandhoppers CRUSTACEA AMPHIPODA

Abstract: The aim of the present review is to combine knowledge of locomotor activity rhythms with that of compass orientation in littoral arthropods. Talitrid amphipods (the sandhoppers) represent a good biological model in the fields of animal orientation and biological rhythms. The paper examines the activity rhythms of different species of sandhoppers (mainly Talitrus saltator), as well as the chronometric mechanisms of compensation for the apparent motion of the sun and moon that these animals use in zonal recovery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 62 publications
2
24
0
1
Order By: Relevance
“…Talitrid amphipods constitute the main animal biomass in sandy beaches and play an important role in the supralittoral environment (Griffiths et al, 1983;Wildish, 1988;McLachlan and Brown, 2006). The sandhopper Talitrus saltator is a well-established model species for biomonitoring human pressure and pollution on sandy beaches (Barca-Bravo et al, 2008;Ugolini et al, 2004Ugolini et al, , 2005Ugolini et al, , 2012Ungherese et al, 2010aUngherese et al, ,b, 2012 and for ecology and behavior (Pardi and Papi, 1953;Wildish, 1988;Ugolini et al, 1999;Ugolini, 2003Ugolini, , 2006. Despite their key ecological relevance for carbon cycling on the damp band of sandy beaches, to date there are very limited reports on T. saltator-associated gut microbial flora (Nuti et al, 1971;Martineti et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Talitrid amphipods constitute the main animal biomass in sandy beaches and play an important role in the supralittoral environment (Griffiths et al, 1983;Wildish, 1988;McLachlan and Brown, 2006). The sandhopper Talitrus saltator is a well-established model species for biomonitoring human pressure and pollution on sandy beaches (Barca-Bravo et al, 2008;Ugolini et al, 2004Ugolini et al, , 2005Ugolini et al, , 2012Ungherese et al, 2010aUngherese et al, ,b, 2012 and for ecology and behavior (Pardi and Papi, 1953;Wildish, 1988;Ugolini et al, 1999;Ugolini, 2003Ugolini, , 2006. Despite their key ecological relevance for carbon cycling on the damp band of sandy beaches, to date there are very limited reports on T. saltator-associated gut microbial flora (Nuti et al, 1971;Martineti et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring the direction of image motion along the sea-land axis may help them to keep to a straight line, to monitor their progress and to correct displacements by wind with respect to Optic flow and sea-land orientation in the sandhopper Talitrus saltator Alberto Ugolini* the direction indicated by the sun compass. Note that the other orienting cues sandhoppers have been shown to rely on, such as the sun and the landscape panorama (for reviews, see Pardi and Ercolini, 1986;Ugolini, 2003), cannot be used to monitor progress and to compensate for displacements.…”
Section: Resultsmentioning
confidence: 99%
“…It has long been known Pardi and Papi, 1953) that both the sun and the moon compasses are used by sandhoppers, like Talitrus saltator (Montagu), and the relationships between compass systems of orientation have been investigated (Ugolini et al, 1999b;Ugolini, 2003;Meschini et al, 2008). As pointed out previously (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…the sea-land direction of the home beach); namely, the skylight gradient of luminance (Ugolini et al, 2009). Hence, sandhoppers can use the skylight gradient of luminance even though it allows a less precise directional choice than the other orienting cues (see also Ugolini, 2003). Experiments on compensation for the apparent movement of the sun have demonstrated that the sun compass works even at night (Pardi, 1954;Ugolini et al, 2002) following the 'Talitrus model': when clockshifted sandhoppers (12h inverted) are released under the sun (during their subjective night), they are able to compensate for the apparent movement of the sun following an internal model in which the sun comes back to east from west, passing through south (Pardi, 1954;Ugolini et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation